Industrial Engineering, Enterprise, and Strategy (AACINI - International Journal of Industrial Engineering, 2024)
The first chapter develops the perspective of the evolution of industrial engineering, aiming to understand the assumptions and the conceptual and instrumental foundations upon which its historical development was based.The second chapter progresses in understanding the concept of the company, establishing a basis to effectively apply knowledge and tools related to processes, systems, and data.The third chapter addresses the issue of strategy and strategic planning for organizations, providing a central foundation to guide companies within their competitive segment, particularly with insights for gaining competitive advantages.Finally, as an epilogue, the authors Dr. Antonio A. Arciénaga Morales (UNSA), Dr. Bárbara M. Villanueva (UNSA), Mg. Pablo E. Aguerre (UNLZ-UPE), and Eng. Leonardo G. Rey (UNLZ) highlight some contributions to the discussion on the direction of the Industrial Engineering program: eco-efficiency and circular economy, meta-organizations and new approaches to the company, the impacts of artificial intelligence on decision-making processes, and digital transformation within organizations.
Keywords: Industrial Engineering; Strategic Planning; Digital Transformation